Religious Pluralism and Early Christian Theology - Wilken, Robert Louis (Interpretation, 1986)
Early Christians understood that not every way to God is sound or elevating, that some forms of religion set our hearts on lesser goods, some teach us to honor and venerate improper objects, some abase rather than uplift.